Circuital and Numerical Models for Calculation of Shielding Effectiveness of Enclosure with Apertures and Monitoring Dipole Antenna Inside - Milutinovic, Vesna; Cvetkovic, Tatjana; Doncov, Nebojsa; Milovanovic, Bratislav (Společnost pro radioelektronické inženýrství, 2013)
In this paper, circuital and numerical models of metal In this paper, circuital and numerical models of metal enclosure with apertures are considered for the purpose of accurate shielding effectiveness calculation. An improved circuital model is presented to account for the presence of receiving dipole antenna which is often used in practice to measure the level of electromagnetic field at selected points inside the enclosure. Receiving antenna of finite dimensions could significantly change the EM field distribution inside the enclosure and thus affect the results for SE. TLM method incorporating wire node is used to create a numerical model. Both models are compared in terms of their ability to account for receiving antenna impact on shielding effectiveness of rectangular enclosure with aperture. In addition, comparison of both models is carried out for the case when an array of apertures with different aperture separation is present on one of the enclosure walls whereby the numerical TLM model is additionally enhanced with compact air-vent model.
Keywords: Enclosure; shielding properties; plane wave; apertures; dipole antenna; circuital model; numerical TLM model